The theology of the Old Testament - Davidson, Andrew Bruce, 1831-1902; Salmond, Stewart Dingwall Fordyce, 1837-1905 (Edinburgh, Scotland T and T Clark, 1904)
Includes bibliographical references and indexes.
9th impression, 1955
Keywords: Bible. O.T. -- theology